Natural and Migration Balance of the Population in Sibiu County Between 1992 and 2021 - Raularian RUSU; Ciprian MOLDOVAN; Titus MAN; Elena-Manuela BÎRSĂNUC; Cosmina-Daniela URSU (Studia Universitatis Babeş-Bolyai: Geographia)
Natural and Migration Balance of the Population in Sibiu County between 1992 and 2021. Sibiu County has been characterised by a better demographic situation than the rest of Romania in the past three decades. The birth rate in Sibiu County has been around 10‰ for many years, above the national and regional average. The mortality rate had similar values, around 10‰ for many years, resulting in a natural balance rate around zero. However, during the pandemic (2020-2021), the birth rate dropped, and the mortality rate increased, which determined a negative natural balance rate at the level of Sibiu County, as low as -4.5‰ in 2021. The net migration rate, on the other hand, has been positive every year since 2006, reaching the highest value of 3.41‰ in 2019, right before the pandemic. The positive net migration rate determined also positive values of the total balance rate in Sibiu County between 2006 and 2019, reaching the highest value of 3.13‰ in 2019. However, the steep decline of the natural balance rate during the pandemic also affected the total balance rate, which became negative in both 2020 and 2021. Nevertheless, the total balance rate is expected to reverse back to positive values after the end of the pandemic. Within Sibiu County, the suburbanization is the major recent process that has an important demographic impact. Areas around the city of Sibiu, especially the commune of Șelimbăr and the town of Cisnădie, have experienced a huge demographic growth, due to migration, but also due to the natural balance rate, which increased suddenly because most of the migrants are young families. Similar situations, although at a lower scale, were recorded in other communes around the city of Sibiu, such as Șura Mare, Șura Mică and Cristian, as well as in communes in Hârtibaciu Plateau (Roșia, Nocrich, Vurpăr, Merghindeal, Chirpăr, Iacobeni), characterised by high birth rates. In contrast, many communes in the western and north-western parts of Sibiu County, such as those in Secașe Plateau (Ludoș, Păuca, Loamneș, Apoldu de Jos), Târnava Mare Corridor and the surrounding hills (Micăsasa, Șeica Mare, Axente Sever, Blăjel, Bazna, Alma, Ațel) and even in Mărginimea Sibiului (Tilișca, Râu Sadului, Jina) experienced a population decline due to outmigration and a negative natural balance rate and a negative net migration rate.